Functional characteristics of endosymbiotic picornia-like virus in Diaphorina citri - Shuai Wang; Muhammad Younas; Chengtao Bao; Yuxi Xiao; Inzamam Ul Haq; Jia Lü; Yu Bin; Taiyun Wei; You Li (Virus Research)
The Asian citrus psyllid (Diaphorina citri) is the primary vector for Candidatus Liberibacter asiaticus (CLas), which is the causative agent of Huanglongbing (HLB). In recent years, increasing attention has been given to the endosymbiotic viruses harbored within D. citri, particularly Diaphorina citri picorna-like virus (DcPLV). However, the epidemiological distribution, biological effects, and role of DcPLV in pathogen transmission remain largely uncharacterized. This study investigates the field prevalence, transmission modes, and biological impacts of DcPLV in D. citri populations collected from 17 regions in China between 2023 and 2024. Detection of DcPLV revealed a widespread distribution, with an average infection rate of 35.18 %. Temporal monitoring in Gutian orchard further showed that DcPLV maintains consistently high infection levels throughout the year. The analysis of transmission showed that DcPLV is transmitted vertically from parents to offspring and horizontally from plant hosts. Biological assessments showed no significant effects of DcPLV on reproduction and adult longevity. Additionally, tissue-specific RT-qPCR revealed virus localization in the midgut and salivary glands, with viral accumulation progressively increasing during nymphal development and continuing into teneral adult. Furthermore, results demonstrated that DcPLV infection significantly enhanced CLas acquisition and accumulation in D. citri, which may contribute to increased vector competence. These findings provide novel insights on the interactions between DcPLV, the D. citri, and CLas.